Marine litter in the seas and oceans - Do we communicate the problem enough? - Funduk, Marina; Farkaš, Anamarija; Janković, Maja (Crisis Management Days, 2024)
INTRODUCTION Marine litter is one of the fastest growing threats to the marine ecosystem with environmental and economic consequences. Litter is released in the sea exclusively due to human activities on land or at sea. The results of the research indicate that about 12 million tons of plastic litter enters the Mediterranean annually. Plastic pollution is still on the rise and could quadruple by 2050 without an action to prevent it at all levels. (Environmental Investigation Agency, n.d.) Irrespective of a number of policy initiatives (action plans, programmes and projects) related to the reduction of marine litter at the global, EU and national levels, this problem is generally not clearly and intensively communicated to the general public. Therefore, this paper provides an overview of the situation related to marine pollution in the Republic of Croatia. It gives an overview of recent communication campaigns with a description of promotional and educational messages related to marine litter. Based on the conducted analyses, there is a certain gap between the increasing marine litter and the insufficient communication of it to the general public. Therefore, the paper overlooks a set of measures for more active communication of this problem to the general public as one of the key measures for reducing marine litter in the future and as one of the most persistent elements of blue growth. METHODOLOGY The paper uses the desktop analysis method, which will provide extensive national and international literature review (studies, research, scientific, professional papers and books) related to the topic of marine litter. Using the method of the Internet and social networks search, information on communication campaigns related to marine litter issue will be collected in order to assess the level of public awareness. The comparative analysis of good practice exams related to communication about marine litter will be carried out. Based on the synthesis of the analysis of the situation and collected examples of good practices in communicating marine litter topics, a proposal will be prepared for decision-makers to communicate these topics more intuitively and to formulate communication messages more clearly. THE RESULTS Litter is released in the sea from various sources: by direct and indirect entry into the sea from the mainland, most often through rivers, drainage systems or wind, and by activities at sea. The main land sources of litter are coastal activities, i.e. unregulated landfills of urban areas on the coast of the sea or rivers, drainage systems, litter washed into storm drains and waterways and wind-blown landfill litter from the coast and tourist activities (Lebreton et al., 2018). The increase of the population on the coast and intensive economic activities, especially tourism, maritime transport and fisheries and aquaculture, have resulted in an increased input of litter into the coastal and marine environment of the Adriatic Sea (Santoro, et.al., 2018). The problem of marine litter is increasingly visible and evident in the Republic of Croatia, and the knowledge of its problems largely corresponds to the situation in other parts of the Mediterranean (Bule et.al., 2020). Significant amounts of microplastics have been recorded in the Adriatic and its impact is not limited to the environment, but affects air, water, food, including salt. Plastic can contain certain concentrations of toxic components up to 1000 times higher than normal in the marine environment. The key objectives for public policies related to the reduction of marine litter in Croatia are (1) to establish a marine litter management system, (2) to improve the waste management information system, (3) to continuously implement education and information activities and (4) to strengthen international cooperation on tackling marine litter. Up until now several significant communication activities and tools have been implemented in Croatia to raise awareness of marine litter, such as the campaign For our Beautiful Country, WWF Campaign on Marine Litter, Green Clean-up and Blue Clean-up Campaigns. Comparative analysis of implemented campaigns in Croatia with global campaigns like Ocean Conservancy Campaign: Trash Free Seas, campaigns organised by Clean Seas and Sea Shepherd shows that there are a number of possibilities for more intensive promotion of marine litter in the Republic of Croatia. One of the key measures to strengthen the communication of this issue is the organization of information - educational campaigns for the interested public on the prevention of marine litter. (Thiel M. et. al., 2023). Informative and educational campaigns should be carried out at the local level in the coastal area for the local population, local interest groups, economic subjects (hospitality accommodation services, tourism, transport, fisheries, etc.), associations, NGOs, schools, and for the local media. At the national level, communication includes the following target groups: the general public/citizens of the Republic of Croatia and tourists visiting Croatia, relevant institutions at the national level, relevant institutions at the EU and international level, educational and scientific institutions, employers, employers' associations, craft and other business interest groups, civil society organizations involved in environmental and nature conservation programs and projects, general media (national newspapers, websites, radio and television) and specialized media.